1995
DOI: 10.1248/bpb.18.1487
|View full text |Cite
|
Sign up to set email alerts
|

Immunostimulatory and Antitumor Activities of Monoglycosylceramides Having Various Sugar Moieties.

Abstract: Ten kinds of monoglycosylceramides (MonoCers), having the same ceramide portion and different sugar moieties, were synthesized and their immunostimulatory and antitumor activities were examined. The manner of combination between sugar and ceramide has been demonstrated to affect the manifestation of immunostimulatory and resultant antitumor activities of MonoCers, and in the case of D-MonoCers having the D-sugar, alpha-D-MonoCers (sugar combined to ceramide in an alpha-configuration) show stronger activities t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 0 publications
0
32
0
Order By: Relevance
“…Recombinant mouse IL-12 and IL-18 (rmIL-12 and rmIL-18) were purchased from R&D Systems. ␣-Galactosylceramide (␣GalCer; (2S,3S,4R)-1-O-(␣-D-galactopyranosyl)-N-hexacosanoyl-2-amino-1,3,4-octadecanetriol) was synthesized at Kirin Pharmaceuticals (18,19).…”
Section: Reagents and Absmentioning
confidence: 99%
“…Recombinant mouse IL-12 and IL-18 (rmIL-12 and rmIL-18) were purchased from R&D Systems. ␣-Galactosylceramide (␣GalCer; (2S,3S,4R)-1-O-(␣-D-galactopyranosyl)-N-hexacosanoyl-2-amino-1,3,4-octadecanetriol) was synthesized at Kirin Pharmaceuticals (18,19).…”
Section: Reagents and Absmentioning
confidence: 99%
“…The role of NKT cells in tumor immunity was not appreciated until it was discovered that ␣GalCer, which had been shown to have antitumor properties (45)(46)(47), was a strong agonist for NKT cells (37). Thereafter, a large number of studies confirmed the antitumor activity of NKT cells stimulated by ␣GalCer in vivo (48,49) or by IL-12 (50).…”
Section: Type I Nkt Cells In Tumor Immunity and Immune Regulationmentioning
confidence: 99%
“…Anti-tumor effect caused by α-GalCer injection has been shown in mouse tumor models Motoki et al, 1995;Morita et al, 1995). Subsequently, protective roles of NKT cells stimulated by α-GalCer were confirmed by liver and lung metastasis models in mice using B16 melanoma cells and Lewis lung carcinoma cells, respectively (Kawano et al, 1998).…”
Section: Anti-tumor Effects Of-galcermentioning
confidence: 95%